-3(6x+9)+1=

Simple and best practice solution for -3(6x+9)+1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(6x+9)+1= equation:


Simplifying
-3(6x + 9) + 1 = 0

Reorder the terms:
-3(9 + 6x) + 1 = 0
(9 * -3 + 6x * -3) + 1 = 0
(-27 + -18x) + 1 = 0

Reorder the terms:
-27 + 1 + -18x = 0

Combine like terms: -27 + 1 = -26
-26 + -18x = 0

Solving
-26 + -18x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '26' to each side of the equation.
-26 + 26 + -18x = 0 + 26

Combine like terms: -26 + 26 = 0
0 + -18x = 0 + 26
-18x = 0 + 26

Combine like terms: 0 + 26 = 26
-18x = 26

Divide each side by '-18'.
x = -1.444444444

Simplifying
x = -1.444444444

See similar equations:

| x=12000(.04) | | 3(40+d)=4(37-d) | | 4x+4=2-1 | | 4x+b=2-1 | | 9=2b-12 | | 6(v-5)+6= | | 2x+25=31 | | 3lnx-ln32=lnx/2 | | .05(x)-.06(y)=-185 | | -6(-5-10k)= | | x^2(-2x-7)=0 | | 5(x+3)-10=2(x+31) | | 6x+27=-4x-3 | | (4y+4)-(2+3y)=5 | | 2(5x+3)=3x+20 | | -3x+8+5x=-4 | | x-8=80/10 | | 7(1-6p)= | | 2x+1=-4x-11 | | .04(x)+.06(x)=100.8 | | 5y^2-80= | | (5n-6)(3n+5)=0 | | x=540-3x+8 | | 3n+3=-9-2n+8 | | x*tanx=64 | | 4/5=a=1 | | 212.5=.04(x) | | 9f-6=51 | | 6x^2/3x-1 | | -v^2+5v+14=0 | | Z^7=1-3i | | -v+5v+14=0 |

Equations solver categories